2019
DOI: 10.35942/ijcab.v3ivi.77
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Resources and Strategy Implementation in Non-Profit Organizations; A Case of Kenya Medical Research Institute, Kenya

Abstract: Most NPOs in Kenya have not fully embraced the use of strategic plans due to the difficulties involved in development implementing of strategic plans. There are many factors that hamper implementation of strategic planning an organisation including inadequate financial resources, human resources, technological competences and organisational culture. The aim of the study was to determine the influence of organizational resources on Strategy Implementationin Non-Profit Organizations with a key focus on The Kenya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Within Kenya's school, Kariuki, Maiyo, and Ndiku (2016) suggested that strategy implementation explained the most impact on performance, hence guaranteeing going-concern status for the institutions investigated. A related study that corroborated Kariuki et al (2016) was by Ngui and Maina (2019). According to the scholars, strategy implementation measures (strategy evaluation, allocation of resources, organization structure, and organization policies) have a positive and significant effect on Winchester Farm Ltd's going concern (Ngui & Maina, 2019).…”
Section: Empirical Review Strategy Execution and Business Continuitymentioning
confidence: 78%
See 2 more Smart Citations
“…Within Kenya's school, Kariuki, Maiyo, and Ndiku (2016) suggested that strategy implementation explained the most impact on performance, hence guaranteeing going-concern status for the institutions investigated. A related study that corroborated Kariuki et al (2016) was by Ngui and Maina (2019). According to the scholars, strategy implementation measures (strategy evaluation, allocation of resources, organization structure, and organization policies) have a positive and significant effect on Winchester Farm Ltd's going concern (Ngui & Maina, 2019).…”
Section: Empirical Review Strategy Execution and Business Continuitymentioning
confidence: 78%
“…A related study that corroborated Kariuki et al (2016) was by Ngui and Maina (2019). According to the scholars, strategy implementation measures (strategy evaluation, allocation of resources, organization structure, and organization policies) have a positive and significant effect on Winchester Farm Ltd's going concern (Ngui & Maina, 2019). The implication of these findings suggests that if significant changes in firm performance are attributable to strategy implementation, the firm will continue in business.…”
Section: Empirical Review Strategy Execution and Business Continuitymentioning
confidence: 79%
See 1 more Smart Citation
“…According to Mwai et al (2018), organisational resources are an organization's assets, talents, capabilities, and intangible possessions that are valuable, uncommon, unreplicable, and nonsubstitutable and that when combined give an organisation a strategic edge. The tangible and intangible assets a company utilises to select and carry out its strategy are called resources (Ngui & Maina, 2019). The internal resources of the various businesses in the same industry are frequently diverse (Jiang, 2014).…”
Section: Resource Allocationmentioning
confidence: 99%
“…Organizational resources were defined as an organization's assets, skills, capabilities, and intangible possessions that are valuable, rare, inimitable, and non-substitutable, which when combined provide an organisation with a strategic advantage (Mwai et al, 2018). Resources are the tangible and intangible assets a firm uses to choose and implement its strategies (Ngui & Maina, 2019). Internal resources of the different firms in the same sector are usually heterogeneous (Jiang, 2014).…”
Section: Resource Allocationmentioning
confidence: 99%